Arsitektur Mikroservis untuk Interoperabilitas Data: Transformasi Integrasi Layanan Smart Village ke Smart City - Esa Firmansyah; Alif Gumelar Syah Moeslim; Rani Rahmayani (Telkom University, 2026)
Smart Village implementations often face data silo challenges due to the lack of efficient integration between village-level systems or city government systems (Smart City), limiting cross-level data synchronization and utilization. This study aims to design a flexible, scalable, and reliable Smart Village to Smart City data interoperability architecture at the architectural integration level to support population administration, licensing, and social assistance services. The proposed methodology adopts a software engineering approach based on the Software Development Life Cycle (SDLC), focusing on requirements analysis, domain-based service decomposition, and microservices architecture design grounded in modern Service-Oriented Architecture (SOA) principles. The proposed architecture integrates synchronous communication through REST APIs managed by an API Gateway and asynchronous communication through Apache Kafka as a message broker to enable real-time or near real-time data update events in distributed environments. The design results indicate that the microservices-based approach with API Gateway and Kafka enhances interoperability, reduces direct coupling between systems, and provides greater flexibility for village service development without disrupting the stability of central systems at the district or city level. Therefore, this architecture has the potential to serve as an adaptive integration framework for the digital public service transformation from Smart Village to Smart City.